Implementation Of Mamdani Fuzzy Logic In The Assessment System Of Merdeka Belajar Kampus Merdeka (MBKM) Activities: Case Study Of Mathematics Study Program At Bangka Belitung University - Baiq Desy Aniska; Randa Trezenki; Afina Shabirah; Novia; Lianawati (Jurnal Sisfokom)
This study aims to apply Mamdani fuzzy logic in the assessment system of the Merdeka Belajar Kampus Merdeka (MBKM) activity to evaluate the effectiveness of student participation. This study was conducted on students of the Mathematics Study Program, Bangka Belitung University, class of 2021, involving four aspects of assessment: teamwork, basic skills, problem solving, and technological innovation. The method used is a descriptive quantitative approach with data processing using MATLAB software. Each input variable is converted into a fuzzy value through triangular and trapezoidal membership functions, followed by the preparation of if-then rules, Mamdani inference, and defuzzification using the centroid method. The results of the analysis show that the fuzzy system is able to produce an objective final assessment and in accordance with the assessor's policy, where students with dominant values ​​at a high level get a final score of 83.7 and are categorized as "good". This study proves that Mamdani fuzzy logic is effective as a tool in the evaluation process of MBKM based on soft skills and hard skills in a comprehensive and measurable manner.